Optimizing the Compaction Characteristics and Strength Properties of Gravelly Soils in terms of Fine Contents - Mingzhi Zhao; Gang Liu; Longxiang Deng; Yangang Li (Advances in Materials Science and Engineering)
Gravelly soils are widely adopted as civil construction materials in engineering practice. Although the influence mechanism of fine contents (FCs) on the mechanical behavior of gravelly soils has been emphasized in the previous studies, few discuss the compaction and strength properties concurrently. Besides, FCs of gravelly soils were discussed separately in many cases regardless of the variation in water content. In this study, modified Proctor compaction test and medium-sized triaxial test were performed to investigate the mechanical properties of gravelly soils containing different magnitudes of fine contents. It is shown that an optimum FC exists for gravelly soils although the value of the optimum FC varies with grading curves of the coarse-grained portion. By adjusting FC in the gravelly soils, not only could the maximum dry density ρdmax be improved but also the optimum saturation degree Sropt rises significantly, and synchronously, the minimum air void ratio vamin decreases notably. Besides, fine particles are just right to fill with the voids formed by the coarse-grained skeleton for the optimum FC sample. The soil structure corresponding to the optimum FC status can be termed as a densely filled skeleton structure, which is the densest and most stable. As fine contents increase or decrease from the optimum value, soil structure will loosen and deteriorate the mechanical properties. In addition, the increase in water content has quite different effects on strength properties of gravelly soils with different FCs in a triaxial test due to the opposite effects of pore water softening and negative pore pressure strengthening. Such results are expected to provide guidance for the preparation of gravelly soils in engineering practices.